2010
DOI: 10.3109/13682822.2010.519372
|View full text |Cite
|
Sign up to set email alerts
|

Speech perception in noise by monolingual, bilingual and trilingual listeners

Abstract: The results replicate previous findings of poorer speech perception in noise with bilingual speakers compared with monolinguals and extend the findings to trilingual speakers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
68
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 29 publications
(59 reference statements)
7
68
3
Order By: Relevance
“…When comparing the two bilingual groups, it is possible to identify that the SGI, that learned the second language after 6 years of age, presented better results, statistically significant (right ear and total) and with significant tendency (left ear) than the SGA, which went through simultaneous learning process. This data disagrees with the authors who defend the existence of critical periods of learning (14) and who claim that the earlier a second language is acquired the lesser are the disadvantages in speech perception (19) . This idea is based on the statement of neuroscientist on children being more efficient learners than adults (14) .…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…When comparing the two bilingual groups, it is possible to identify that the SGI, that learned the second language after 6 years of age, presented better results, statistically significant (right ear and total) and with significant tendency (left ear) than the SGA, which went through simultaneous learning process. This data disagrees with the authors who defend the existence of critical periods of learning (14) and who claim that the earlier a second language is acquired the lesser are the disadvantages in speech perception (19) . This idea is based on the statement of neuroscientist on children being more efficient learners than adults (14) .…”
Section: Discussioncontrasting
confidence: 54%
“…Studies have shown that, even achieving a high proficiency level in the second language, the bilingual individuals present greater difficulty when subjected to tests in their second language (18,19) . Therefore, in this study, the assessment was conducted in Portuguese, native language of all participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies indicate that participants who speak English as a second language perform worse on competing signal speech tests compared to native-English speakers (Tabri et al, 2011;van Wijngaarden et al, 2002;Zokoll et al, 2013), although the effect of non-nativeness on digit-triplet recognition in noise is small (Kaandorp et al, 2015). It is therefore important that different norms should be investigated for the South African English digit-in-noise hearing test as South Africa consists of a multilingual population.…”
Section: Discussionmentioning
confidence: 99%